Differential diagnosis and treatment for bacterial vaginosis - Chilova R.A; G.F. Proklova; N.V. Goncharenko (LCC «Medicine-Inform», 2020)
R.A. Chilova, G.F. Proklova, N.V. Goncharenko Sechenov University, Moscow, Russian Federation Bacterial vaginosis is a non-inflammatory infectious syndrome associated with the suppression of normal vaginal microflora by polymicrobial associations of anaerobes and Gardnerella vaginalis. Vaginal microflora is composed mainly of lactobacilli and, in addition, bifidus bacteria and propionic bacteria. Recent studies have demonstrated that bacterial vaginosis is caused not only by G. vaginalis but many other microbes as well thus affecting drug choice for this disorder. A need for the prevention, early diagnosis, and treatment for bacterial vaginosis is accounted for by qualitative changes in vaginal microflora which contribute to various complications threatening female reproductive health. Bacterial vaginosis is associated with various complications of pregnancy, i.e., preterm birth, infections of chorion, intrauterine fetal death etc. Bacterial vaginosis is known to be significantly associated with infertility. Therefore, early diagnosis is of crucial importance, the treatment should be performed before pregnancy. This article analyzes published studies on modern diagnostic and effective therapeutic modalities for bacterial vaginosis. Treatment success mostly depends on drug choice with maximum effect on most causative agents of bacterial vaginosis but minimum toxicity. Keywords: vaginal microflora, bacterial vaginosis, la ctobacilli, differential diagnosis, complications, treatment, clindamycin. For citation: Chilova R.A., Proklova G.F., Goncharenko N.V. Differential diagnosis and treatment for bacterial vaginosis. Russian Journal of Woman and Child Health. 2020;3(1):-43. DOI: 10.32364/2618-8430-2020-3-1-39-43.